A Study of Metaphor Translation from Anak Semua Bangsa into Its English Version Child of All Nations - Valentino, Yosafat Barona; Metekohy, Marschall Eirence (Indonesian Journal of English Language Studies (IJELS), 2016)
This paper aims to find what types of metaphor are there in the novel Anak Semua Bangsa and the strategies for translating those metaphors employed by the translator in translating Anak Semua Bangsa into Child of All Nations. In order to do so, the researchers employed Dunn’s (2015) types of metaphors for data classification and Shi’s (2014) strategies of trans- lating metaphors. The data were taken from the novel Anak Semua Bangsa for the source lan- guage data and Child of All Nations for the translation version. This study finds that there are three types of metaphors found in Anak Semua Bangsa novel, i.e. modulated (62.67%), source-target (29.33%), and interpretive (8.00%). The translator of Anak Semua Bangsa was likely to employ either using literal translation or changing the metaphor to meaning strate- gies for translating metaphors. In conclusion, regardless for what purposes the translation is, the translation product should preserve above all the meaning rather than the forms. Keywords: translation, metaphor, Anak Semua Bangsa, child of all nations